2016
DOI: 10.1038/tp.2016.110
|View full text |Cite
|
Sign up to set email alerts
|

Reduced frontal-subcortical white matter connectivity in association with suicidal ideation in major depressive disorder

Abstract: Major depressive disorder (MDD) and suicidal behavior have been associated with structural and functional changes in the brain. However, little is known regarding alterations of brain networks in MDD patients with suicidal ideation. We investigated whether or not MDD patients with suicidal ideation have different topological organizations of white matter networks compared with MDD patients without suicidal ideation. Participants consisted of 24 patients with MDD and suicidal ideation, 25 age- and gender-matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 78 publications
9
68
0
Order By: Relevance
“…Additionally, alterations of WM microstructure have also been positively correlated with depression severity. Previous studies have repeatedly reported that WM microstructural abnormalities may play a role in the emergence of depression and suicidal ideations in patients with MDD (Jia et al, 2014;Myung et al, 2016). Our findings suggest that the forceps minor and the cingulum may play an important role in integrating motivational information leading to loss of pleasure experience and depression.…”
Section: Discussionsupporting
confidence: 53%
“…Additionally, alterations of WM microstructure have also been positively correlated with depression severity. Previous studies have repeatedly reported that WM microstructural abnormalities may play a role in the emergence of depression and suicidal ideations in patients with MDD (Jia et al, 2014;Myung et al, 2016). Our findings suggest that the forceps minor and the cingulum may play an important role in integrating motivational information leading to loss of pleasure experience and depression.…”
Section: Discussionsupporting
confidence: 53%
“…MDD patients have been found to have increased mediodorsal thalamus but reduced dorsal PFC activity and reduced connectivity between the medial thalamic and the dorsal PFC at rest or in response to negative affective stimuli . Reduced thalamic‐PFC structural connectivity observed in MDD patients may provide an anatomical basis for the current findings . The weakened thalamus connectivity with the PFC may be associated with abnormal norepinephrine transmission, based on recent findings of elevated norepinephrine transporter availability in the mediodorsal thalamus and significant association with impaired attention in MDD .…”
Section: Discussionmentioning
confidence: 60%
“…Several issues need to be further addressed. Studies showing altered thalamo‐frontal structural connections may provide an anatomical basis for the current findings . However, strong functional connections commonly exist between regions with no direct structural connection, rendering the straightforward inference of functional connectivity from structural connectivity impractical .…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations